2011
DOI: 10.1111/j.1748-0361.2010.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

“If Only Someone Had Told Me …”: Lessons From Rural Providers

Abstract: Purpose-Health care providers face challenges in rural service delivery due to the unique circumstances of rural living. The intersection of rural living and health care challenges can create barriers to care that providers may not be trained to navigate, resulting in burnout and high turnover. Through the exploration of experienced rural providers' knowledge and lessons learned, this study sought to inform future practitioners, educators, and policy makers in avenues through which to enhance training, recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 22 publications
(25 reference statements)
1
53
0
Order By: Relevance
“…8 There was a moderate positive relationship between feelings of professional isolation and whether the community where the practice was located was isolated (r s = 0.430, P < .01), indicating that the responding physician assistants felt professionally isolated when their practices were geographically isolated. When the isolation questions were analyzed for a correlative association to burnout, there was a weak positive relationship between the physician assistants' feelings of professional isolation and the DP (r s = 0.293, P < .01) and EE (r s = 0.273, P < .01) subscales and a moderate negative relationship between this variable and PA (r s = 20.410, P < .01), whereas geographical isolation of their practice did not correlate to burnout as strongly as the feeling of professional isolation (DP, r s = 0.169, P < .05; EE, r s = 0.091, P > .05; PA, r s = 20.175, P < .05).…”
Section: Resultsmentioning
confidence: 84%
“…8 There was a moderate positive relationship between feelings of professional isolation and whether the community where the practice was located was isolated (r s = 0.430, P < .01), indicating that the responding physician assistants felt professionally isolated when their practices were geographically isolated. When the isolation questions were analyzed for a correlative association to burnout, there was a weak positive relationship between the physician assistants' feelings of professional isolation and the DP (r s = 0.293, P < .01) and EE (r s = 0.273, P < .01) subscales and a moderate negative relationship between this variable and PA (r s = 20.410, P < .01), whereas geographical isolation of their practice did not correlate to burnout as strongly as the feeling of professional isolation (DP, r s = 0.169, P < .05; EE, r s = 0.091, P > .05; PA, r s = 20.175, P < .05).…”
Section: Resultsmentioning
confidence: 84%
“…Additionally, other research drawing on qualitative interviews conducted with rural providers of health care has found that those working in rural areas must confront a variety of unique challenges – such as maintaining confidentiality, establishing trust, limited resources, and isolation – suggesting that rural context may exacerbate the already challenging work of substance abuse treatment (Chipp et al, 2011). While limited research has confirmed the challenges of delivering substance abuse treatment in rural contexts, further research focusing on rural substance abuse treatment providers using a detail-rich qualitative approach is needed to understand the unique challenges of working in rural contexts (Chipp et al, 2011; Johnson, Brems, Warner, & Roberts, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While limited research has confirmed the challenges of delivering substance abuse treatment in rural contexts, further research focusing on rural substance abuse treatment providers using a detail-rich qualitative approach is needed to understand the unique challenges of working in rural contexts (Chipp et al, 2011; Johnson, Brems, Warner, & Roberts, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, repeated demonstrations of integrity by economically established countries towards all people affected by mental illness and its burden throughout the world is a precondition for ethically sound and humane healthcare. Moreover, intensive and more appropriately attuned ethics education is critically important in understanding and addressing mental health inequalities and in the preparation of clinicians caring for people living with mental illness (Chipp et al, in press; Hoop, DiPasquale, Hernandez, & Roberts, 2008; Jain, Dunn, & Roberts, in press; Lehrmann, Hoop, Hammond, & Roberts, 2009; Roberts, Johnson, Brems, & Warner, 2008) in rural and underserved areas.…”
Section: Introductionmentioning
confidence: 99%